BUREAUCRATIC REFORM OF KPKNL MALANG: IT’S EFFECT ON PERFORMANCE AND SERVICE QUALITY - Nuha, Muh. Ulin (Faculty of Administrative Science, Universitas Brawijaya, 2024)
Indonesia's public service organizations have been conducted to implement ZI-WBK (Zona Integritas Wilayah Bebas Korupsi) as an effort for bureaucratic reform. The reform is measured by six areas of change: human resource management, change management, performance accountability, public service strengthening, technical arrangement, and supervision strengthening; KPKNL Malang, as a public service organization, is committed to increasing its general performance. This study uses a qualitative approach to know how ZI-WBK affects performance and service quality in KPKNL Malang. Using NVivo 12 Pro to analyze the interview results, this study shows that bureaucratic reform significantly affects performance and service quality in KPKNL Malang. Stakeholder testimonials and service quality scores demonstrate it.